Diphenyl diselenide-modulation of macrophage activation: Down-regulation of classical and alternative activation markers - Rupil, Lucia (2012)
Diphenyl diselenide ((PhSe)2), a simple organoselenium compound, possesses interesting pharmacological properties that are under extensive research. As macrophages respond to microenvironmental stimuli and can display activities engaged in the initiation and the resolution of inflammation, in the present report we describe the ability of (PhSe)2 to modulate the macrophage activation. Our data indicate that (PhSe)2 could inhibit the NO production in a dose-dependent fashion in peritoneal macrophages activated by LPS or treated with vehicle alone. We could demonstrate that this effect correlated with a reduction in the expression of the inducible NO synthase in (PhSe)2-treated cells. Furthermore, (PhSe)2 suppressed the production of reactive oxygen species, diminished the activity of the arginase enzyme, and the accumulation of nitrotyrosine modified proteins in LPS-stimulated macrophages. This compound also diminished the antigen presentation capacity of classically activated macrophages, as it reduced MHCII and CD86 expression. In addition, (PhSe)2 modulated the alternative activation phenotype of macrophages. Dexamethasone-activated macrophages presented higher production of IL-10 and CD206, which were both down-regulated by the addition of (PhSe)2. These results suggest that (PhSe)2 possesses antioxidant and anti-inflammatory activities in classically-activated macrophages. We could demonstrate that (PhSe)2 can be also utilized to modulate the alternative activation phenotype of macrophages.